Use of the TikTok App as a Learning Tool for Elementary Science: The Effect of Style on Objects - Feri Novriadi,; Yanti Fitria, (International Conference on Elementary Education, 2023)
21st century learning is a change in learning patterns and directing the curriculum through an approach that was originally teacher centered to become student centered. In addition, teachers as educators must also be able to utilize IT in learning activities. The use of IT is certainly a challenge for teachers to be more creative and innovative in making learning media. The learning media used must be in line with technological advances. Learning media must also be attractive, inexpensive and easy to use by students. One application that is loved by today's generation is TikTok. TikTok is the easiest and cheapest app to get. With a variety of features so that it can be easily used by teachers and students. The use of the TikTok application is expected to be an interactive learning media that can help teachers convey learning to students, so that students can understand and accept the learning process. This study aims to determine the effectiveness of using the TikTok application as a science learning medium on the effect of force on objects. This study uses descriptive qualitative research and data collection techniques through interviews, observation and documentation. The results of the study indicate that the use of TikTok in learning is effective, it can be seen from the enthusiasm of students in learning and the material presented can and is easily accessible by students.